Differences of onset and duration of judo specialization between male and female Olympic judo athletes - Narazaki, N.; Watanabe, R. (Association for the Scientific Studies on Judo, Kodokan, 2021)
This study aimed to examine differences of onset and duration of judo specialization between male and female Olympic judo athletes. Seven male and seven female Japanese judo athletes were recruited as subjects. The quantitative analyses showed that the onset of judo specialization was significantly earlier in female athletes than that in male athletes (mean age of male = 16.3±1.4 years; mean age of female = 14.2±0.8 years, p<0.05). On the other hand, there was no significant difference in the duration of judo specialization between male and female Olympic judo athletes (p=0.103). The results obtained in this study suggest that 1) judo coaches need to individualize training program, guidance and advice for junior athletes, dependent on differences of onset and duration of judo specialization, even in the same age group, and 2) to consider potential risks of injury and demotivation especially for female athletes who underwent earlier onset of specialization, and 3) to understand different maturation process between male and female athletes which may require gender specific instructions.